2020
DOI: 10.3390/nu12113581
|View full text |Cite
|
Sign up to set email alerts
|

Are Obese Patients with Autism Spectrum Disorder More Likely to Be Selenium Deficient? Research Findings on Pre- and Post-Pubertal Children

Abstract: Selenium is involved in many metabolic pathways that are critical for life. Information concerning the metabolic effects of selenium in autism spectrum disorder (ASD) and obesity is still conflicting and incomplete. The pre- and post-pubertal selenium profiles of patients with ASD and obesity have not yet been investigated. The goal of the study was to examine selenium content before and after puberty in euthyroid children diagnosed with ASD, compared to age-matched neurotypical controls, with respect to overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 51 publications
2
3
0
Order By: Relevance
“…This mechanism may also have a positive influence on the protective effect of selenium on CKD. This may not be the case in obese people because they suffer from high levels of oxidative stress [46] often accompanied by multiple metabolic diseases (including obesity itself [47]), which are strongly correlated with the selenium levels in the human body [48,49]. The results found in our study in our disease subgroups supported this view.…”
Section: Discussionsupporting
confidence: 73%
“…This mechanism may also have a positive influence on the protective effect of selenium on CKD. This may not be the case in obese people because they suffer from high levels of oxidative stress [46] often accompanied by multiple metabolic diseases (including obesity itself [47]), which are strongly correlated with the selenium levels in the human body [48,49]. The results found in our study in our disease subgroups supported this view.…”
Section: Discussionsupporting
confidence: 73%
“…This study also identified a correlation between BMI and Se levels within males. This is consistent with previous findings in older children; a negative correlation has been seen between Se levels and overweight or obese patients, particularly those with an ASD diagnosis ( Blazewicz et al, 2020 ). The underlying mechanism behind this is not clear, though suggestions have been made that food selectivity is higher in children with ASD, therefore Se deficiency may be the result of differences in food consumption ( No Author List, 2020 ).…”
Section: Discussionsupporting
confidence: 93%
“…For both schizophrenia (11,32,33) and autism (12,34,35), reduced Se levels have been chronicled in the literature, albeit there are many exceptions (36)(37)(38), and it is unclear whether this represents a cause or consequence of these conditions. Of particular significance to our results is a recent report examining the Se status of 287 Polish children, which were divided into four groups, corresponding to: (1) autism spectrum disorder (ASD) with obesity, (2) ASD without obesity, (3) non-ASD with obesity, and (4) non-ASD without obesity (12). Observed Se levels were lowest in ASD patients with obesity and highest in non-ASD patients without obesity, with differences between groups being highly significant (p < 0.001) for serum, urine, toenail samples.…”
Section: Discussionmentioning
confidence: 99%
“…Common symptoms associated with Se-deficiency include hypothyroidism, cardiomyopathy, compromised immunity, fatigue, and cognitive deficits (8)(9)(10). Also, altered serum Se levels have been documented in both autism and schizophrenia (11,12), and it is hypothesized that redox imbalance during neurodevelopment increases risk for these neuropsychiatric conditions (13,14).…”
Section: Introductionmentioning
confidence: 99%